PDE4 as a target for cognition enhancement. (September 2013) - Richter, Wito; Menniti, Frank S.; Zhang, Han-Ting; Conti, Marco
<x xml:space="preserve">Abstract</x> Introduction: The second messengers cAMP and cGMP mediate fundamental aspects of brain function relevant to memory, learning, and cognitive functions. Consequently, cyclic nucleotide phosphodiesterases (PDEs), the enzymes that inactivate the cyclic nucleotides, are promising targets for the development of cognition-enhancing drugs. Areas covered: PDE4 is the largest of the 11 mammalian PDE families. This review covers the properties and functions of the PDE4 family, highlighting procognitive and memory-enhancing effects associated with their inactivation. Expert opinion: PAN-selective PDE4 inhibitors exert a number of memory- and cognition-enhancing effects and have neuroprotective and neuroregenerative properties in preclinical models. The major hurdle for their clinical application is to target inhibitors to specific PDE4 isoforms relevant to particular cognitive disorders to realize the therapeutic potential while avoiding side effects, in particular emesis and nausea. The PDE4 family comprises four genes, PDE4A-D, each expressed as multiple variants. Progress to date stems from characterization of rodent models with selective ablation of individual PDE4 subtypes, revealing that individual subtypes exert unique and non-redundant functions in the brain. Thus, targeting specific PDE4 subtypes, as well as splicing variants or conformational states, represents a promising strategy to separate the therapeutic benefits from the side effects of PAN-PDE4 inhibitors.